The effectiveness of child and adolescent sports engagement in China: an analysis of China’s results for the 2016–2022 Global Matrix report cards on physical activity - Changqing, Xiang; Jie, Zhao; Tengku Kamalden, Tengku Fadilah; Wenting, Dong; Hua, Luo; Ismail, Normala (Nature Publishing Group, 2023)
China strives to become a leading sports nation. Through implemented policies and programs, Chinese children and adolescents have shown notable advancements and improvements in their engagement in physical activity in recent years, indicating an overall positive trend. However, some indicators exhibit a concerning “inversion phenomenon”. This study utilizes data from three surveys conducted between 2016 and 2022 by the Active Healthy Kids Global Alliance. By comparing current ratings with those from 2016 and 2018, both cross-sectionally and longitudinally, significant obstacles in promoting physical activity and health among Chinese children and adolescents are revealed, with persistently low scores. The 2022 Global Matrix 4.0 report ranks Chinese children and adolescents 53rd out of 57 surveyed countries, with an overall average physical activity score of D. Similarly, the average score for sources of influence ranks at 53rd. Consequently, the establishment of an integrated school, family, and social sports promotion mechanism, led by the government, becomes an imperative prerequisite for enhancing the levels of physical activity and overall health among children and adolescents.